THE RIGHT TO A FAVORABLE ENVIRONMENT - Гатамов, Хатаї Севіндік огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Goal: determination of the features of ensuring the right to a favorable environment. Methods of research: analysis and study of legal documents containing provisions on the right to a favorable environment. Results: the right to a healthy environment has not been included in such fundamental international human rights instruments. Much more progress has been achieved in relation to the law in question at the national level, where the right to a favorable environment is enshrined in some new constitutions. The collective nature of the right to a favorable environment arises from the fact that, as will be shown below, the purpose of establishing this right is to protect environmental objects that are important not for one particular person, but for residents of a whole region or even for the entire planet. It seems that the recent tendency to recognize the law in question, both at the national and international levels, is obvious. And yet, and today, it seems, there is no universal document that would unequivocally and clearly enshrine the human right to the environment. Discussion: the proposal to include this issue on the agenda of international organizations. The system of standards in the field of environmental protection is successfully developing at the international level. In particular, within the framework of the European Union, more than 50 standards in this area are currently in force; at the same time, various types of standards are applied, which are specialized according to various environmental protection objectives. So-called exposure standards and primary protection standards set the maximum concentration of hazardous chemicals (for example, lead) in drinking water or ambient air. Environmental quality standards are a quantitative expression of the criteria for compliance with environmental requirements in relation to various natural objects (air, bathing reservoirs, reservoirs for separation, etc.). They are established either for a specific source or for a particular class of pollutants and can be applied in the whole region, country or Union. In addition to the pollution arising during the production cycle, the actual products of production can also be sources of pollution when they are used or buried. Therefore, the Union establishes environmental safety standards that regulate both the production process and the composition of the product being produced. Thus, environmental standards define the technical boundaries of state behavior in relation to the natural environment, put obstacles to unacceptable changes in this environment and, in essence, define the limits of the state’s population’s right to a safe environment.